Support needed by parents when a child's mental well‐being is threatened : A qualitative study of views of experts‐by‐experience - Putkuri, Tiina; Latva-Korpela, Irene; Häkkinen, Mikko (Wiley, 2025)
Background
In situations where a child's mental well-being is threatened, the parents also need support. The available support has been perceived as insufficient by both parents and professionals.
Aim
To explore the views of experts-by-experience of the support needed by parents when a child's mental well-being is threatened.
Methods
A qualitative study with a phenomenological approach was conducted in Finland. The data were collected in six focus group interviews during the autumn of 2022. The participants (n = 26) were adult experts-by-experience who had experienced either mental well-being challenges in their own childhood (before the age of 18 years) or experienced the mental well-being challenges of a child from the role of a parent. The data were analysed using inductive content analysis.
Results
The support needed by parents in situations where the mental well-being of their child is at risk consists of support for parenting, support for sharing and support for surviving.
Conclusion
Parents whose child's mental well-being is at risk, need support both for their own well-being and for their ability to support their child's well-being. Support is needed not only from professionals but also from peers.